Pengaruh Earning Per Share, Net Profit Margin dan Firm Size terhadap Harga Saham (Studi Kasus pada Perusahaan Sektor Telekomunikasi yang Terdaftar di BEI Periode 2021-2024) - Salsabila, Raisha; Khairi, Himmatul (ARZUSIN, 2026)
The development of digital transformation and the increasing public demand for internet services have made the telecommunications sector one of the strategic sectors attracting investor attention in the capital market. However, research specifically examining the influence of earnings per share (EPS), net profit margin (NPM), and firm size on the stock prices of telecommunications sector companies for the 2021–2024 period remains limited. This study aims to analyze the influence of EPS, NPM, and firm size on the stock prices of telecommunications sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study used a quantitative approach with a causal design. The research sample consisted of 17 telecommunications sector companies selected using purposive sampling, with a total of 68 observational data. Data were collected through documentation of companies’ annual financial statements and analyzed using multiple linear regression with the assistance of SPSS version 21. The results showed that EPS and NPM had no significant effect on stock prices, whereas firm size had a significant effect on the stock prices of telecommunications companies. Simultaneously, EPS, NPM, and firm size had a significant effect on the stock prices of telecommunications companies. The conclusion of this study affirms that company size is a fundamental factor that more strongly determines stock prices than EPS and NPM partially in telecommunications sector companies. These findings contribute to the development of signalling theory by showing that companies’ fundamental information can serve as a signal for investors in making investment decisions, while also providing practical implications for investors and telecommunications companies in considering fundamental factors as a basis for investment and business strategies.